Assessment of infant sleep: how well do multiple methods compare?. Issue 10 (6th August 2018) - Camerota, Marie; Tully, Kristin P; Grimes, Melissa; Gueron-Sela, Noa; Propper, Cathi B
Abstract: The current study compares sleep variables obtained from videosomnography, actigraphy, and sleep diaries, three of the most common sleep assessment methods used in infant sleep studies. Using a sample of 90 African American 3-month olds, we compare correlations and discrepancies for seven sleep variables across each of the three pairs of assessment methods for one night of a week-long sleep study. These seven variables are indicative of sleep schedule (e.g. sleep onset time, rise time), duration (e.g. sleep period, sleep time, wake time), and fragmentation (e.g. night wakings, longest sleep period). We find that across all sleep assessment methods, correlations are highest for variables indicative of sleep schedule, and lowest for variables indicative of sleep fragmentation. Comparing the magnitude and significance of the discrepancies, we find that actigraphy and sleep diaries significantly overestimate sleep period duration and underestimate the number of night waking episodes, compared with videosomnography. Actigraphy and sleep diaries were more concordant with one another than with videosomnography. Epoch-by-epoch analyses indicated that actigraphy had low sensitivity to detect wakefulness, compared with videosomnography. Contrary to our hypothesis, the discrepancies between sleep assessment methods did not vary widely based on infant sleep location (own room vs. parent's room) or sleep surface (own bed vs. parent's bed). Limitations and implications of these findings for future research are discussed.